Non-local effects on pedestal kinetic ballooning mode stability. (11th April 2017) - Saarelma, S; Martin-Collar, J; Dickinson, D; McMillan, B F; Roach, C M
Abstract: The H-mode pedestal height plays an important role in determining the global confinement of the tokamak plasma. In type I ELMy H-mode the ultimate limit for the pedestal pressure at constant width is set by the ideal MHD peeling-ballooning modes (PBMs) that are thought to be the trigger for the ELMs. However, the PBM criterion does not uniquely determine the pedestal. Increasing the width of the pedestal, the marginally peeling-ballooning stable pedestal height increases as well. The second criterion for the pedestal is set by the transport processes in the pedestal that limit the gradient between the ELMs. One candidate for driving this transport is the kinetic ballooning mode (KBM) that is driven by the pressure gradient (Snyder et al 2009 Nucl. Fusion 49 085035). The KBM growth rate increases very rapidly after the critical pressure gradient is exceeded leading to very stiff profiles with the pressure gradient clamped near to the stability limit. In the local linear gyrokinetic analysis of experimental MAST and JET plasmas we have found that, like the n = ∞ ideal MHD ballooning modes, the KBMs can access locally so called second stability if the magnetic shear becomes low enough (Dickinson et al 2011 Plasma Phys. Control. Fusion 53 115010; Saarelma et al 2013 Nucl. Fusion 53 123012). However, in the pedestal region the local assumption that the equilibrium can be considered radially constant for the investigated modes is no longer justified. In this paper we revisit the KBM analysis using a global code ORB5 to investigate whether second stability access exists for KBMs. We find that counter to the local analysis, the global KBM stability is not sensitive to the magnetic shear in the pedestal region. At sufficiently high β (but still below the ideal peeling-ballooning limit) the pedestal region becomes KBM unstable regardless of the amount of bootstrap current assumed in the equilibrium reconstruction. However, just as in local analysis, the mode is stabilised by reducing the pressure gradient. This suggests that KBMs can regulate the pedestal pressure gradient during the ELM cycle even when local analysis finds them stable due to high bootstrap current.